1986
DOI: 10.1063/1.337275
|View full text |Cite
|
Sign up to set email alerts
|

Infrared reflectance evaluation of chemically vapor deposited β-SiC films grown on Si substrates

Abstract: We use infrared reflectance from 400 to 4000 cm−1 to evaluate cubic SiC films grown by chemical vapor deposition on Si substrates. From different regions of the spectra we determine precise film thicknesses, estimate carrier concentrations in highly doped specimens, observe roughness at both film surfaces, and detect conducting regions at the interface. We show how the roughness and the interfacial conducting region introduce nonideality into the spectra. The method is nondestructive and the information can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 22 publications
4
29
0
Order By: Relevance
“…1 a pronounced peak at 794 cm -1 is shown, attributed [12] to SiC, as mentioned before. This is in accordance with the literature data: Spitzer et al [13,17] and Holm et al [18], found that crystalline SiC film 0.06 pm thick grown on an Si substrate has a strong absorption band at 794 cm-x, as well as a strong reflection peak at the same position. This is exactly the same as seen in Figs 1 and 3.…”
Section: Discussionsupporting
confidence: 91%
“…1 a pronounced peak at 794 cm -1 is shown, attributed [12] to SiC, as mentioned before. This is in accordance with the literature data: Spitzer et al [13,17] and Holm et al [18], found that crystalline SiC film 0.06 pm thick grown on an Si substrate has a strong absorption band at 794 cm-x, as well as a strong reflection peak at the same position. This is exactly the same as seen in Figs 1 and 3.…”
Section: Discussionsupporting
confidence: 91%
“…The reflectivity of the Si substrate is considered almost constant over the whole range. The spectrum of the sample containing only the buffer layer exhibits a weak peak at 790 cm -1 (ω TO ) [16,17]. This indicates that the carbonized layer is composed only of a SiC-like crystal, which is consistent with the XRD results.…”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 86%
“…These results are essentially the same as those obtained from 3C-SiC/Si in which a highly doped interfacial layer exists for modeling the decreasing fringe contrast. 7 After the interfacial layer was determined, we found the thickness of the epitaxial layer (including the interfacial layer) to be ¾6.6 š 0.2 µm.…”
Section: Resultsmentioning
confidence: 99%